Gender and Struggles for Equality in Mining Resistance Movements: Performing Critique against Neoliberal Capitalism in Sweden and Greece - Landén, Angelika Sjöstedt (Social Inclusion, 2018)
This article explores the intersections of gender and centre-periphery relations and calls for theoretical and political involvement in gendered struggles against colonial and capitalist forces across different national contexts. The article raises questions about the possibility of resisting inequality and exploitation arising from capitalist expansion and extraction of natural resources in Sweden and Greece, outside of urban contexts. It does so by highlighting women’s role in protest movements in peripheral places and questioning power relations between centre and periphery. The article also argues that making visible women’s struggles and contributions to protest movements brings about vital knowledge for realizing democratic worlds that do not thrive on the destruction of natural resources and the institutionalization of inequalities.